Aliphatic chains grafted cellulose nanocrystals with core-corona structures for efficient toughening of PLA composites. (1st June 2022) - Niu, Weidong; Guo, Yunfeng; Huang, Wei; Song, Lili; Xiao, Zefang; Xie, Yanjun; Wang, Yonggui
Abstract: To promote the replacement of nondegradable petrochemical-based polymers with green polylactic acid (PLA) materials, aliphatic chains-grafted cellulose nanocrystals (ECNCs) were prepared and used as nanofillers to overcome the disadvantage of poor toughness of PLA. ECNCs with core-corona structures were obtained by modifying cellulose nanocrystals (CNC) with valeryl chloride, octanoyl chloride, dodecanoyl chloride, and stearoyl chloride. ECNCs consists of a cellulose crystalline core and a soft esterified corona layer with aliphatic chains. Among the diverse ECNCs, the obtained EOCNC by esterification of octanoyl chloride exhibited most efficient enhancement of the toughness of PLA. Specifically, PLA/EOCNC-1% film displayed the best elongation at breakage of 108%, which was 6.4 times that of pure PLA. The esterified outer layer of ECNCs, which improves the interfacial compatibility, is one of the key factors contributing to toughening of PLA. These ECNCs with core-corona structure open up new directions for the application of PLA advanced composites. Graphical abstract: Unlabelled Image